Small for gestational age and obesity: epidemiology and general risks - Hyo-Kyoung Nam; Kee-Hyoung Lee (Korean Society of Pediatric Endocrinology, 2018)
Children born small for gestational age (SGA) have several life-long consequences. Previous epidemiological studies investigated from childhood to adulthood reported that a number of chronic diseases originate in the prenatal period. With the emerging era of obesity epidemic, more concerns are related to being obese than being short-statured in SGA children. The exact mechanisms are uncertain; however, growth hormone-insulin-like growth factor axis disturbance by fetal programming and accelerated postnatal weight gain contributed to central adiposity in SGA children. In this review, we summarized the definitions and prevalence of SGA, epidemiology, and general risks of obesity in SGA children. Early interventions, before and after birth, are needed for healthy catch-up growth to prevent later obesity and related complications.